Frailty and Cardiovascular Health - James, Kirstyn; Jamil, Yasser; Kumar, Manish; Kwak, Min J.; Nanna, Michael G.; Qazi, Saadia; Troy, Aaron L.; Butt, Jawad H.; Damluji, Abdulla A.; Forman, Daniel E.; Orkaby, Ariela R. (Journal of the American Heart Association, 2024)
The incidence of frailty and cardiovascular disease (CVD) increases as the population ages. There is a bidirectional relationship between frailty and CVD, and both conditions share several risk factors and underlying biological mechanisms. Frailty has been established as an independent prognostic marker in patients with CVD. Moreover, its presence significantly influences both primary and secondary prevention strategies for adults with CVD while also posing a barrier to the inclusion of these patients in pivotal clinical trials and advanced cardiac interventions. This review discusses the current knowledge base on the relationship between frailty and CVD, how managing CVD risk factors can modify frailty, the influence of frailty on CVD management, and future directions for frailty detection and modification in patients with CVD.